An Innovative Study on Teaching Basic Music Theory in Chinese Higher Education Institutions - Wu, Weixin (Pacific International Journal, 2024)
This study explores the effectiveness of innovative teaching strategies in the basic music theory curriculum at the Music College of Zhaoqing University, Guangdong Province, China. With the ongoing reforms in Chinese music education, there is a growing interest in integrating modern pedagogical approaches to improve student engagement, understanding, and the practical application of music theory. The research employs a quantitative approach, utilizing surveys to assess students’ learning experiences, comprehension, and feedback on the current music theory teaching methods. The study evaluates students' performance in key music theory concepts, including intervals, chords and harmony, rhythm, key signatures, and melodic structures, while also investigating the challenges faced by students and teachers. Results suggest that while most students are satisfied with the clarity and pace of the course material, there is significant variation in their understanding of complex concepts, such as rhythm and melodic structures. The study highlights the need for targeted instructional interventions to address these gaps and recommends further exploration of interdisciplinary approaches and longitudinal studies to track the impact of innovative methods over time. By offering valuable insights into the ongoing transformation of music education in China, this study provides a foundation for future curriculum development and pedagogical improvements in the field.